Influência do pH sobre a estabilidade de suspensões de alumina estabilizadas eletroestericamente - Sales, Luciano Leal de Morais; Souza, Antonio Gouveia de; Soledade, Luis Edmundo Bastos; Santos, Iêda Maria Garcia dos; Rodrigues Neto, João Batista; Longo, Elson [UNESP]; Paskocimas, Carlos Alberto (Sociedade Brasileira de Química, 2007)
In this work, aqueous suspensions of aluminas with different particle sizes were evaluated. The effect of pH on the electrosteric stabilization using PMAA-NH4 (ammonium polymethacrylate) as deflocculant was studied. The amount of deflocculant was optimized and rheologic properties were determined at four different pH values. Sedimentation was also evaluated. For suspensions with pH 4, an electrostatic mechanism of stabilization was observed, probably due to a flat adsorption of PMMA- on the alumina surface, leading to a small efficiency in relation to steric stabilization. For a suspension with pH 12, the steric mechanism of stabilization prevails. Suspensions with pH 7 and 9 present a higher flocculation degree. In relation to particle size, A-1000 samples present a smaller particle size, leading to a smaller interparticle distance (IPS), making stabilization more difficult.
Influence of pH on the stability of alumina suspensions electrosterically stabilized
Keywords: pH; polymethylmethacrylate; alumina